Impacts of distributed generation on the protective devices in the PEA distribution system - Pauranee Satphaisarnkit; Weerakorn Ongsakul; Singh, Jai Govind; Marpaung, Charles O.P.; PEA; Asian Institute of Technology Education Cooperation Project; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Traditional Provincial Electricity Authority (PEA) distribution system is radial in nature and supplied through substations. The presence of distributed generation (DG) provides considerable benefits from both engineering and economic viewpoints. However, the existing network was not designed for its integration. Protection selectivity is altered in the magnitude, duration and direction of fault current which may lead to problems related to incorrect operation. This thesis presents the impacts of DG on the protection system in PEA distribution system using DIgSILENT PowerFactory as a tool. The study divided into five case studies, considering sizes and connection position of a synchronous DG. The expected result can be a beneficial technical guideline to improve PEA protection system.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Distributed generation of electric power -- Thailand